PENGARUH ORGANISASI REMAJA MASJID USSISA ALA TAQWA DESA PEMATANG CERMAI KECAMATAN TANJUNG BERINGIN KABUPATEN SERDANG BEDAGAI DALAM MENINGKATKAN SHALAT BERJAMAAH DI MASJID - Wahyudi, Muhammad (Fakultas Agama Islam, 2020)
The main problem of this research is how the role of the youth of the Ussisa Ala Taqwa mosque in increasing congregational prayers in Pematang Cermai Village, Tanjung Beringin District, Serdang Bedagai Regency. The sub-problems are: 1) What is the work program for the youth of the Ussisa Ala Taqwa mosque in increasing congregational prayers? This type of research is a descriptive qualitative study with a sociological and management approach. Interviews were conducted with mosque administrators, mosque youth, congregations and community leaders. Data collection methods are carried out by making observations or observations, interviews, and documentation. Then the data is analyzed using data reduction techniques, data display, verification and data conclusion. The results of this study indicate that there are six work programs of youth at the Ussisa Ala Taqwa mosque in increasing congregational prayers in Pematang Cermai Village, Tanjung Beringin District, Serdang Bedagai Regency, namely routine recitation of the taklim council, basic recitation of the Al-Qur'an Education Park (TPA), conducting recitation or religious lectures, Commemoration of Islamic Holidays (PHBI), calligraphy training and holding clean Fridays. In carrying out these activities, there are still obstacles faced by youth mosques, namely factors of activity, weather factors, discipline factors and financial factors. His efforts are to keep activating the previously prepared programs and providing reading books that provide motivation about congregational prayer and the disadvantages of those who are reluctant to pray in congregation. The implication of this research is that mosque youth should understand the situation and condition of the community, cooperate with the community, as well as the government, religious leaders to provide support to mosque youth in the form of morals or material.